Outcomes of Isolated Medial Patellofemoral Ligament Reconstruction for Recurrent Patellar Instability in Ehlers-Danlos Syndrome. Issue 5 (31st May 2022) - Nemunaitis, James; Parikh, Shital N
Background: Ehlers-Danlos syndrome (EDS) -hypermobility type is characterized by generalized hyperlaxity which is considered to be a risk factor for patellar instability. Surgery is discouraged in this subset of patients due to high rates of failure. The outcomes following isolated Medial Patellofemoral Ligament Reconstruction (MPFLR) for patellar instability in EDS population has not been reported. Purpose: To analyze re-dislocation rates and patient-reported outcomes of isolated MPFLR for recurrent patellar instability in adolescents with EDS. The second purpose of the study was to compare allograft vs autograft for MPFL reconstruction in this specific population. Methods: Between 2010 and 2016, 21 knees in 16 consecutive patients underwent isolated MPFLR reconstruction for recurrent patellar instability. The diagnosis of EDS-hypermobility type, was confirmed by genetics for all patients, with Beighton score as the chief determinants. All patients underwent isolated MPFL reconstruction with hamstring tendon graft. Recurrent dislocation rate and patient-reported outcomes, including Pedi-IKDC, Kujala Score, HSS Pedi-FABS, Banff Instability Instrument 2.0, and KOOS Knee Survey were collected at minimum 2 year follow-up. Results: The mean age of the cohort was 15.4 years (range 13-18 years). All patients were females. 16 knees had atraumatic mechanism of patellar dislocation. 2 patients had an osteochondral fracture. 5 patients underwent bilateral MPFLR. 9 patients had prior surgeries on their knee; 6 were failed patellar stabilization procedures but only 1 was failed MPFLR. 14 knees had hamstring autograft and 7 had hamstring allograft. At minimum 2 years follow-up, 3 of 21 knees (14.2%) had recurrent dislocation. There were no other complications. The mean pedi IKDC, Kujala, Pedi-FABS, and BANFF scores were 66.62 (95% CI 8.52), 73.5 (95% CI 8.68), 6.73 (95% CI 2.86) and 57.15 (95% CI 10.24) respectively. The overall mean KOOS pain subscale was 73.85 (95% CI 9.95) and KOOS symptoms subscale score was 48.54 (95% CI 5.56). There were no significant differences in outcome scores and re-dislocation rates between autograft and allograft (p>0.5). There was no significant correlation between functional score and Beighton score. Conclusion: EDS-related patellar instability are primarily atraumatic in origin without an osteochondral fracture. Patients had significant improvements in function following isolated MPFLR at minimum 2 years follow-up. However, these functional improvements were less than historical controls. Re-dislocation rate of 14% is higher than normal population. EDS and joint hypermobility is not a contraindication to MPFLR but caution is recommended in managing patient expectations.